P(A)SH Syndrome: Case Presentation and Short Update of Related Disorders - Kordeva, Simona; Hristova, Alice; Broshtilova, Valentina; Tchernev, Georgi (Acta medica (Hradec Kralove), 2024)
Hidradenitis suppurativa (HS) is a chronic inflammatory disease that is frequently associated with syndromes, such as those within the PAPA spectrum. Syndromic HS presents unique management challenges, as it often shows resistance to conventional therapies. Pyoderma gangrenosum is a rare inflammatory neutrophilic dermatosis that is often seen in association within the spectrum of autoinflammatory diseases. The PAPA spectrum disorders include a group of autoinflammatory diseases characterized by mutations in the PSTPIP1 gene or by clinical manifestations that closely resemble or overlap with those of PAPA syndrome. Each syndrome (PASH, PAPASH, PsAPASH, PASS, PAC, and PAMI syndrome) in this spectrum highlights specific inflammatory pathways and symptoms, providing insight into targeted therapeutic approaches. Here, we present a rare case of incomplete PASH (pyoderma gangrenosum and hidradenitis suppurativa) syndrome successfully managed with a standard combination of antibiotics (ceftriaxone and metronidazole) and corticosteroids (methylprednisolone), followed by immunosuppressant (azathioprine) and corticosteroids (dexamethasone). We review both novel and established/standard treatment options, with an emphasis on treatment outcomes. Conventional therapies remain both effective and affordable, providing valuable alternatives for patients.
Keywords: Humans; corticosteroids; lidé středního věku; PAPA syndrome; PASH syndrome; pyoderma gangrenosum; Syndrome; lidé; antibakteriální látky; antibiotics; imunosupresiva; Hidradenitis Suppurativa; Immunosuppressive Agents; Anti-Bacterial Agents; Male; syndrom; Middle Aged; azathioprine; Pyoderma Gangrenosum; mužské pohlaví; hidradenitis suppurativa